Crossing Borders: Geographical, Linguistic, and Cultural - Antropov, Alexander (Canadian Journal for the Study of Adult Education, 2020)
This is a personal narrative about my transformative journey as an educator through the calamities of the failed perestroika in the Soviet Union and cultural shocks of living in the United States and Canada. I analyze the factors contributing to my academic abilities that allowed me to graduate with a PhD in mathematics from a university in Russia and become a deputy dean in another university in Moscow. I explain why revolutionary social changes in Russia in the 1990s made me feel as a foreigner in my home country and encouraged me to leave for the United States. I examine what gave me the strength to start anew my professional life abroad from part-time jobs to full-time teaching positions in public schools and universities. Finally, I reflect on my transformative experiences during my doctoral studies at a Canadian provincial university, earning a PhD in education.